Winner's Curse Correction and Variable Thresholding Improve Performance of Polygenic Risk Modeling Based on Genome-Wide Association Study Summary-Level Data - Shi J. (Public Library of Science (PLoS), 2018)
10.1371/journal.pgen.1006493